Platform for collection from heterogeneous web sources and its application to a semantic repository organization at SeDiCI: Preliminaries - De Giusti, Marisa Raquel (2009)
Presentation of a web collection platform designed to relate and unify information available on different standard web sources with a view to creating a userbrowseable thematic repository. The platform will be used at the Intellectual Creation Diffusion Service combined with ontologies and thesaurus to provide improved data sorting. Data is currently spread on web resources and traditional search engines return ranked lists with no semantic relation among documents. Users have to spend a great deal of time relating documents and trying to figure out which ones fully address the issue domain. It is only after locating similarities and differences that information fragments are applied to the user s work, enabling knowledge creation. The proposed platform sorts out the different theme domain functioning modules to allow their use in various knowledge areas. Development includes two agents that searches data base stored URLs, one is capable of identifying bookmarked pages, interpreting labels and providing rules for extracting information and storing it in a RDF data file; on the other hand, the other agent is in charge of getting related URLs from the given one. After this stage, homogenization is applied and transformed information is sorted out according to domain ontologies. The platform allows for more efficient automatic extraction processes and information search among heterogeneous sources that represent the same concepts using different standards.